(untitled) (Sustainability in Debate, 2018)
Even though remote from public authorities, the riverside Amazon has been able to adapt to and overcome struggles. There are similarities between the local vegetation’s connection with water rhythms and communities’ adaptive capacity to forest ecosystem and rivers. This riverside Amazon, that lives in its own rhythm and reproduces itself while showing its weaknesses and also its resilience, was discovered during a scientific expedition held in the Uatumã Sustainable Development Reserve (Uatumã SDR). The research team that integrates the bilateral Project Brazil-France designated by SINBIOSE “Système d’INdicateurs de BIOdivérsité Ã l’uSage des actEurs: Biodiversité terrestre et aquatique” (Biodiversity Indicators System for the use of actors: Land and aquatic biodiversity) made the journey in August 2017